Etomidate anesthesia in chicks: Effect of xylazine - MOUSA, Y. (Journal of the Hellenic Veterinary Medical Society, 2021)
The current study aimed to evaluate the etomidate anesthetic action, its toxicity profile and safety alone and to determine the benefit of xylazine coadministration to enhance its anesthetic duration, efficacy and to reach a state of balanced anesthesia in chicks. By using the up-and-down technique, it was found that the hypnotic Median Effective Dose (ED50) of the etomidate was 4.30 mg/kg, IM, whereas the acute Median Toxic Dose (TD50) was 17.90 mg/kg, IM in the chicks. In response, the calculated Therapeutic Index (TI) and Standard Safety Margin (SSM) indicate that the etomidate has a wide safety margin. Etomidate injection at 4, 8 and 16 mg/kg, IM yields a significant dose-response and dependent hypnosis in the chicks by evaluating the onset of the righting reflex loss, its period and regaining from it. The combination composed of etomidate and xylazine at 5 mg/kg, IM for each, reduced the onset of hypnosis and significantly distended its period besides a significant rise of the recovery time when compared with the group receiving etomidate alone. At the same time, this coadministered drugs elicited a significant raise in analgesic efficacy. Concerning plasma glucose, Alanine Transaminase (ALT) and Aspartate Transaminase (AST) concentrations, neither etomidate nor etomidate plus xylazine differ significantly from the control group. The results of this study propose the likelihood of using etomidate as an anesthetic agent for short surgical trials in the chickens that can be more effective by using xylazine to yield balanced anesthesia without causing significant side effects.